2018
DOI: 10.3390/su10114289
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Scale Event and a Big Impact—Is This Relationship Possible in the World of Sport? The Meaning of Heritage Sporting Events for Sustainable Development of Tourism—Experiences from Poland

Abstract: The theoretical part of this article presents the meaning of sporting events for the tourism industry and the importance of sporting events at a small scale, as well as heritage sporting events for sustainable development of tourist destinations. The literature review shows that there is a clear research gap with respect to the analysis of economic and social impacts of small-scale events. The empirical research was conducted by the method of a diagnostic survey during three sporting events of different rank, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 46 publications
0
70
0
3
Order By: Relevance
“…Recently, researchers focused mainly on mass, popular, street runs/cycling events in the context of their meaning for sporting events and active tourism or in the context of motivation for running/cycling or health implications for runners/cyclists [22][23][24][25][26][27][28][29]. Sporting events have been analyzed as a tourist phenomenon [30][31][32][33][34] and the social identity of athletes is rarely investigated in this area. The dynamic growth of running sports events is a result of different factors.…”
Section: Ultramarathons-from Extreme To Mainstream: Discussionmentioning
confidence: 99%
“…Recently, researchers focused mainly on mass, popular, street runs/cycling events in the context of their meaning for sporting events and active tourism or in the context of motivation for running/cycling or health implications for runners/cyclists [22][23][24][25][26][27][28][29]. Sporting events have been analyzed as a tourist phenomenon [30][31][32][33][34] and the social identity of athletes is rarely investigated in this area. The dynamic growth of running sports events is a result of different factors.…”
Section: Ultramarathons-from Extreme To Mainstream: Discussionmentioning
confidence: 99%
“…There is a feeling among residents that they are a small community with spatial and economic limitations, which however possesses a strong cultural identity that should be strengthened and nurtured, above all, in the younger age groups to create a true competitive advantage both in the case of sports events and in tourism communication. Both the quantitative and qualitative analysis demonstrated that intangible social dimensions may be clearer [50]. The research results reveal that the residents pay great attention to sports events, even small-scale ones.…”
Section: Do Small-scale Sports Events Represent a Stimulus For Hostinmentioning
confidence: 81%
“…In some cases, sports events represent one of the most important attractions for the tourist destination, causing serious losses in the case of cancellation [47]. The literature presents an important evolution also with respect to the issue of sustainability at small-scale sports events and their impact on destinations, which in most cases are rural or peripheral areas rather than cities or areas with strong urbanization [42,[48][49][50]. There are several studies that document how small-scale sports events represent a form of sustainable tourism for communities [2,42].…”
Section: Small-scale Sports Eventsmentioning
confidence: 99%
“…When planning investments, the investor must take into account the needs of tourists. Festivals as an element embedded in the local ecosystems of sport, culture and business [41]; • Events related to the sport heritage of the region and other smaller sports events, including mass sporting and recreational events [42].…”
Section: Tourism and Investment Attractivenessmentioning
confidence: 99%